Secure Data Sharing in Cloud Computing Systems: Techniques and Applications - Aeri, Manisha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Secure data sharing in cloud computing systems is critical to protecting data from unauthorized access or manipulation. Conventional data security approaches are insufficient to assure total data protection in the cloud, and new strategies are necessary. Access control, data encryption, tokenization, digital signatures, data masking, data backup and recovery, virtual private networks, firewalls, intrusion detection systems, and cloud access security brokers are among the techniques investigated in this paper for secure data sharing in cloud computing systems. Furthermore, the study investigates safe data sharing applications in a variety of industries, including healthcare, banking, education, government, retail, manufacturing, legal, and non-profit. These examples show how secure data sharing can improve cooperation, efficiency, and trust in a variety of industries. Secure data sharing in cloud computing platforms is critical, and firms must employ adequate security measures to protect their data. Organizations may ensure that their data is secure, available only to authorized individuals, and used to promote cooperation, efficiency, and trust by implementing the methodologies and applications discussed in this paper.